Puzzle : "On a marché sur Charleroi". - Busine, Laurent; Coppee, Philippe-Henri; Olivier, Ghislain; Lorent, Claude (Charleroi : Palais des Beaux-Arts, 1984)
Groupe Puzzle: Coppee, Philippe-Henri ; Fauville, Daniel ; Flemal, Jean-Marie ; Josse, Bernard ; Roch, Alain ; Meli, Giuseppe ; Van Hooland, Philippe ; Michel, Pierre ; Romeo, Jean Carlo ; Dizais, Martin ; Badot, Marco ; Barbier, Guy ; Coppee, Philippe-Henry ; Delepeleire, Damien ; Dizais, Martin ; Frere, Michel ; Lombet, Lucien ; Octave, Jean-François ; Olivier, Ghislain ; Opstael, Dirk ; Villers, Yves
Puzzle "On a marché sur Charleroi", Palais des Beaux-Arts de Charleroi, Octobre 1984
kunstcatalogus
Keywords: Puzzle Groupe